Impact of Glycemic Management on Non-Diabetic Adults Subjected to Mitral Valve Replacement Surgery at Department of Cardiology, BMU - Qumruzzaman, Khondoker; Mahmood, Manzoor; Kadir, ANM Monowarul; Pasha, Mostofa Midhat; Shameem, Md Kibriya; Ahmed, Sayeed; Jamali, Mohammod Zafor Iqbal (University Heart Journal, 2025)
Background: The primary aim of this research was to investigate potential correlations between elevated post-operative blood glucose levels following cardiopulmonary bypass (CPB) and the incidence of morbidity and mortality. Methodology: This cohort analysis was conducted at the Department of Cardiology, Bangladesh Medical University, between January 2023 and January 2024. A total of 75 non-diabetic adult patients undergoing mitral valve replacement (MVR) using CPB were enrolled based on predefined inclusion and exclusion criteria. Participants were stratified into two cohorts based on blood glucose concentrations measured within the first 60 hours post-operatively. Group A (unexposed) included patients with glucose levels ≤10.1 mmol/L, while Group B (exposed) included those with levels >10.1 mmol/L. Post-operative outcomes were monitored throughout the hospital stay. Results: Of the 75 patients, 37 (49.3%) were in Group A and 38 (50.7%) in Group B. Post-operative morbidity was significantly higher in Group B (p = 0.001). Hyperglycemic patients experienced longer ICU stays (p = 0.001). Neurological complications (p = 0.04), renal dysfunction (p = 0.01), and surgical site infections (p = 0.04) were also significantly more frequent in Group B. Hospital stays were longer among hyperglycemic patients (p = 0.004). Mortality was higher in Group B but did not reach statistical significance (p = 0.31). Conclusion: Post-CPB blood glucose levels exceeding 10.1 mmol/L are significant predictors of adverse post-operative outcomes and increased morbidity in non-diabetic patients undergoing MVR. University Heart Journal 2025; 21(2): 64-68